Pharmacoeconomic study of rivaroxaban and acetylsalicylic acid combination use in patients with coronary artery disease and/or peripheral artery disease - N. V. Pogosova; A. V. Panov; A. Yu. Kulikov; V. G. Serpik; V. A. Kulikov (Российский кардиологический журнал)
Aim. Comparative assessment of the economic results of rivaroxaban/acetylsalicylic acid (ASA) combination and ASA monotherapy use in patients with coronary artery disease (CAD) and/or peripheral artery disease (PAD). Material and methods. Based on the results of a large international multicenter, placebo-controlled, randomized clinical trial COMPASS, a model that evaluated the clinical outcomes of rivaroxaban/ASA combination and ASA monotherapy was formed. The economic results using cost and cost-effectiveness analyses, and budget impact analysis for two years were also calculated. The analysis took into account both direct medical costs (expenses for treatment, hospitalization due to complications, rehabilitation) financed under the compulsory health insurance, as well as indirect costs (loss of GDP due to disability or death). The calculation was made by accounting 100,000 patients with CAD and/or PAD.Results. Modeling of clinical outcomes per 100,000 patients based on COMPASS results showed a decrease of stroke prevalence by 649 cases, myocardial infarction — 301 cases, amputations — 478 cases, cardiovascular mortality — 476 cases when using rivaroxaban/ASA combination compared with ASA monotherapy. The cost-effectiveness analysis showed that rivaroxaban/ASA combination has greater clinical efficacy and lower costs in comparison with ASA monotherapy. Budget impact analysis showed that the switching of 100,000 patients with CAD and/or PAD from ASA monotherapy to rivaroxaban/ASA combination leads to budget savings of 1,026 million rubles in two years. This is due to a decrease in the incidence of cardiovascular events.Conclusion. It was found that the use of a rivaroxaban/ASA combination in comparison with ASA monotherapy in patients with CAD and/or PAD can both decrease a number of complications and lead to cost savings, despite the initially higher cost pharmacotherapy.